Study on the non linear characteristic of power transformer and their effect ferroresonance - Shamsuddin, Salizawati (2008)
Ferroresonance can occur in electrical power system and consequently can cause damage such as due to voltage transformer overheating or power transformer overvoltages. This study involves simulation work to simulate various conditions under which ferroresonance can occur in typical extra high voltage substations. The ATP-EMTP simulation program was used to model various power system components and simulate the ferroresonance phenomena. The effects of the non-linear characteristics of power transformers are also studied. Methods to prevent the ferroresonance conditions from occurring and hence avoiding equipment damages and losses were also proposed based on the simulation work.